2015
DOI: 10.1523/jneurosci.2563-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Sound Localization in Two Functionally Distinct Regions of the Auditory Cortex

Abstract: The auditory cortex is necessary for sound localization. The mechanisms that shape bicoordinate spatial representation in the auditory cortex remain unclear. Here, we addressed this issue by quantifying spatial receptive fields (SRFs) in two functionally distinct cortical regions in the pallid bat. The pallid bat uses echolocation for obstacle avoidance and listens to prey-generated noise to localize prey. Its cortex contains two segregated regions of response selectivity that serve echolocation and localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…It has been shown that not only the behavioural responses differ between active and passive hearing in these animals (Goerlitz et al ., ), but also the neural processing of sounds (Suga & Schlegel, ; Schuller, ). For the bat Antrozous pallidus, it was even suggested that actively and passively perceived sounds are processed in two parallel auditory pathways (Razak et al ., , ). Therefore, we assumed that in the bat's SC ‘active’ and ‘passive’ acoustic space may also not be equally represented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that not only the behavioural responses differ between active and passive hearing in these animals (Goerlitz et al ., ), but also the neural processing of sounds (Suga & Schlegel, ; Schuller, ). For the bat Antrozous pallidus, it was even suggested that actively and passively perceived sounds are processed in two parallel auditory pathways (Razak et al ., , ). Therefore, we assumed that in the bat's SC ‘active’ and ‘passive’ acoustic space may also not be equally represented.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Razak et al . () demonstrated that in the auditory cortex of the pallid bat ( Antrozous pallidus ) two sub‐regions exist, which encode the spatial position of noise and echoes, respectively, based on different sound cues. In the noise‐selective region interaural intensity differences and frequency selectivity are the primary cues for representation of 2D acoustic space, whereas, in the region selective for echo‐information encoding of spatial information is dependent on pinna directionality.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that the 2D location representation in the auditory cortex is fundamentally different than in the midbrain [Razak and Fuzessery, 2002;Razak 2011Razak , 2012Razak , 2016Razak et al, 2015]. Pallid bats fly with their ears facing downwards (pinna parallel to ground) when foraging.…”
Section: Neuroethology Of Sound Localizationmentioning
confidence: 92%
“…The FM sweep selective region (FMSR), like the ventral ICc, contains neurons with tuning > 25 kHz and responds selectively to the bandwidths, rates, and direction of FM sweeps in the echolocation call [Razak and Fuzessery, 2006;. The noise selective region (NSR), like the lateral ICc, contains neurons tuned < 35 kHz and responds selectively to noise with energy between 5 and 35 kHz [Razak 2011, Razak et al, 2015. Thus, the segregated functional organization observed in the IC is continued in the auditory cortex.…”
Section: Auditory Cortex and Thalamocortical Connectionsmentioning
confidence: 99%
See 1 more Smart Citation